ANALYSIS OF GEOGRAPHIC INFORMATION SYSTEM OF VULNERABILITY MAPPING TO TSUNAMI IN SOUTH GARUT COASTAL - Nursandi, Ikhsan; Darmawan, Muhammad Lucky; Junaedi, Hamdan; Ulhaq, Tsany Zia; Yuflihan, Naufal Hatta; Sapanji, R.A.E. Virgana Targa (CENTRAL ASIA AND THE CAUCASUS, 2022)
A tsunami disaster can be interpreted as a disaster that can damage the area near the coast and its surroundings, and has a very highly destructive power. This study focuses on evacuation routes, planning the level of danger, and preventing the impact of the tsunami effectively and efficiently. In this study, researchers analyzed the coastal area of South Garut Beach which has a great potential for a tsunami disaster because the South Garut coast is very close to the meeting between Indonesian-Australian plates and Sunda Strait Megathrust. If there is any friction between the plates, it will cause a potential tsunami disaster not only in the coastal area, but also in the villages and seven subdistricts. The Modeling of this hazard impact can be found in three groups; low, moderate, and high. The lowest area has the highest tsunami potential because the lowest land will cause a tsunami to be easier to obtain, which means that it is classified as being hit by a tsunami. In addition, and the last one at altitude of 30 meters and above altitude is classified as safe from the threat of a tsunami. In this study, researchers used an overlay technique on thematic maps such as distance maps from the coastline, elevation areas, slope areas, and distances from rivers. The overlay technique is carried out using the scoring and weighting method.